2022
DOI: 10.21203/rs.3.rs-1870054/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Inhibition of Vesicular Glutamate Transporters (VGLUTs) with Chicago Sky Blue 6B Before Focal Cerebral Ischemia Offers Neuroprotection.

Abstract: Brain ischemia is one of the leading causes of death and long-term disability in the world. Interruption of the blood supply to the brain is a direct stimulus for many pathological events. The massive vesicular release of glutamate (Glu) after ischemia onset induces excitotoxicity, which is a potent stress on neurons. Loading of presynaptic vesicles with Glu is the first step of glutamatergic neurotransmission. Vesicular glutamate transporters 1, 2, and 3 (VGLUT1, 2 and 3) are the main players involved in fill… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…VGLUT1 and VGLUT2 have been shown to in uence the extent of Glu release and subsequent excitotoxic damage (Takamori et al, 2000). Therefore, targeting VGLUTs activity could provide therapeutic bene ts in mitigating the effects of stroke and other neurological diseases (Pomierny et al, 2023;Yan et al, 2020). In our previous studies we showed in in vivo model of brain ischemia, that unspeci c inhibition of VGLUTs, reduced neurological de cit, infarct volume as well as reduced excitotoxicity and neuroin ammation in rats (Pomierny et al, 2023(Pomierny et al, , 2024.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…VGLUT1 and VGLUT2 have been shown to in uence the extent of Glu release and subsequent excitotoxic damage (Takamori et al, 2000). Therefore, targeting VGLUTs activity could provide therapeutic bene ts in mitigating the effects of stroke and other neurological diseases (Pomierny et al, 2023;Yan et al, 2020). In our previous studies we showed in in vivo model of brain ischemia, that unspeci c inhibition of VGLUTs, reduced neurological de cit, infarct volume as well as reduced excitotoxicity and neuroin ammation in rats (Pomierny et al, 2023(Pomierny et al, , 2024.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, targeting VGLUTs activity could provide therapeutic bene ts in mitigating the effects of stroke and other neurological diseases (Pomierny et al, 2023;Yan et al, 2020). In our previous studies we showed in in vivo model of brain ischemia, that unspeci c inhibition of VGLUTs, reduced neurological de cit, infarct volume as well as reduced excitotoxicity and neuroin ammation in rats (Pomierny et al, 2023(Pomierny et al, , 2024. Unfortunately, due to high homology of VGLUTs, there are no speci c and selective inhibitors of VGLUT1, which is known as a main vesicular transporter in the CNS (Thompson et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation